Analisis Implementasi Konsep Green dalam Komponen ASEAN Green Hotel Standard di Glamping Bobocabin The Tavia Puncak, Bogor, Jawa Barat - Jason Djaya Hadinata; Stephanie Rosanto (Lembaga Yasin AlSys, 2026)
Bobocabin The Tavia Puncak is a modular cabin-based glamping accommodation that has implemented various sustainable tourism practices, but its implementation of the green hotel concept has not fully met the ASEAN Green Hotel Standard (AGHS) criteria, particularly in promoting local culture, using environmentally friendly products, and empowering local products. This study aims to analyze the level of implementation of the green hotel concept based on the AGHS components and assess the eligibility of Bobocabin The Tavia Puncak to obtain the certification. This study employed a qualitative approach with a descriptive case study design. Data were collected through field observations, in-depth interviews, documentation, and a literature review and were subsequently analyzed based on the eleven AGHS components, encompassing environmentally friendly policies and operations, the use of environmentally friendly products, cooperation with local communities, human resource development, waste management, energy and water efficiency, air quality, noise control, wastewater management, and the management of hazardous and toxic materials. The results show that the implementation level of the green hotel concept reached 68.75%, with nine of the eleven components meeting most of the AGHS indicators. The highest achievements were found in energy and water efficiency, waste management, and air pollution and noise control. However, the promotion of local culture, water reuse systems, documentation of environmental programs, and the involvement of local micro, small, and medium enterprises still require improvement. This study concludes that Bobocabin The Tavia Puncak has a good level of readiness and is eligible to be proposed for the AGHS certification process, although several supporting components still need to be refined. These findings provide practical implications for accommodation managers in strengthening environmental governance and local community empowerment and serve as a reference for the development of sustainable tourism in the glamping sector.